2022
DOI: 10.1051/alr/2022017
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities: impacts of COVID-19 on Norwegian seafood exports

Abstract: A rapidly growing literature shows that COVID-19 and the measures to contain the spread of the virus can have significant market impacts for seafood. These can be interruptions of production, or reductions in demand directly or indirectly due to supply chain challenges. In this paper we investigate the potential impacts of COVID-19 on seafood exports from Norway, the world's second largest seafood exporter, using highly detailed data from 2016 through May 2021. These data allow us to assess upstream impacts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The question of how Swedish shrimp fishers were impacted is complex since boiled shrimp are consumed both at restaurants as well as bought for private consumption at home. Reduced consumption in restaurants may be offset by increased private consumption at home [3] , [2] . Our primary question is whether covid-19 has caused an actual price change in Swedish shrimp over the course of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The question of how Swedish shrimp fishers were impacted is complex since boiled shrimp are consumed both at restaurants as well as bought for private consumption at home. Reduced consumption in restaurants may be offset by increased private consumption at home [3] , [2] . Our primary question is whether covid-19 has caused an actual price change in Swedish shrimp over the course of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding other studies related to ours, [12] found that small-scale fleets were more negatively impacted compared to large scale fleets in Europe. [3] , [2] found that the impact of Covid-19 on Norwegian seafood export, which is dominated by aquaculture salmon, was limited, and held that the markets and supply chains used by Norwegian seafood exports were sufficiently robust and flexible to accommodate the shocks created by COVID-19. [3] , [2] found that the price effects on the large vessel groundfish fleet in Norway with no significant effects of Covid-19 on the cod price.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation